1990
DOI: 10.1034/j.1399-3054.1990.790219.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane-bound NADH: Fe3+-EDTA reductase and iron deficiency in tomato (Lycopersicon esculentum). Is there a Turbo reductase?

Abstract: 1990. Plasma membrane-bound NADH: Fe'+-EDTA reductase and iron deficiency in tomato {Lycopersicon esculentum). Is there a Turbo reductase? -Physiol. Plant. 79: 339^346.The properties of NADH-dependent Fe^*-EDTA reductase in plasma membranes (PM) from roots of iron-deficient and -sufficient tomato plants \Lycopersicon esculentum L. (Mill.) cv. Abunda] were examined. Iron deficiency resulted in a 3-fold increase of in vivo root iroB-chelate reductase activity with a K^ (Fe'+-EDTA) of 230 M.ln purified root PM, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…Contrary to some reports from higher plants (Cakmak et al 1987;BruÈ ggemann et al 1990), addition of exogenous superoxide dismutase did not decrease the rate of Fe(III) reduction, nor did the addition of exogenous NADH stimulate iron reduction (Table 1). It has been suggested that NADH-dependent peroxidase activity is able to catalyze reduction of extracellular Fe(III) to Fe(II), in a process that also results in a stimulation of O 2 consumption and is sensitive to inhibition by superoxide dismutase (MacrõÁ et al 1992).…”
Section: Resultscontrasting
confidence: 82%
“…Contrary to some reports from higher plants (Cakmak et al 1987;BruÈ ggemann et al 1990), addition of exogenous superoxide dismutase did not decrease the rate of Fe(III) reduction, nor did the addition of exogenous NADH stimulate iron reduction (Table 1). It has been suggested that NADH-dependent peroxidase activity is able to catalyze reduction of extracellular Fe(III) to Fe(II), in a process that also results in a stimulation of O 2 consumption and is sensitive to inhibition by superoxide dismutase (MacrõÁ et al 1992).…”
Section: Resultscontrasting
confidence: 82%
“…In contrast to the reductive capacity for iron chelates which is expressed in iron-stressed roots of dicots and most monocots (Turbo-System), the reduction of ferricyanide is a general feature of all plants and tissues (Standard-System). However, recent investigations on purified plasma membrane vesicles showed that no biochemically distinct enzyme is expressed when plants were starved of iron (7,8,17). The substrate dependence of the reduction of ferricyanide by iron-deficient roots is shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…This hypothesis was supported by findings of Bienfait et al (5) and Romheld and Marschner (6), based on results obtained with intact plants. Initial attempts to demonstrate a direct involvement of PM-bound reductase(s) in the reduction of extracellular Felll using both intact tissue and isolated PM-vesicles have been carried out recently (7,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on ferric reduction of purified PM from iron-deficient and ironsufficient plants were compared with in vivo data and brought the original model into question. In their study, Brtiggemann et al (1990) could not confirm the synthesis of a biochemically distinct enzyme formed under iron stress, but proposed that the in vivo response to iron starvation relies on the enhanced synthesis or activation of a constitutively existing redox system. However, till the time of this work (July 1993), no iron chelate reductase system has been isolated from PM and purified to homogeneity so far.…”
Section: Iron Reductase Systems In Root Plasma Membranesmentioning
confidence: 94%